2020
DOI: 10.5194/tc-14-2869-2020
|View full text |Cite
|
Sign up to set email alerts
|

New gravity-derived bathymetry for the Thwaites, Crosson, and Dotson ice shelves revealing two ice shelf populations

Abstract: Abstract. Ice shelves play a critical role in the long-term stability of ice sheets through their buttressing effect. The underlying bathymetry and cavity thickness are key inputs for modelling future ice sheet evolution. However, direct observation of sub-ice-shelf bathymetry is time-consuming, logistically risky, and in some areas simply not possible. Here we use new compilations of airborne and marine gravity, radar depth sounding, and swath bathymetry to provide new estimates of sub-ice-shelf bathymetry ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…We suggest that this morphology was generated as the highs were overridden and eroded by a formerly expanded TG and Thwaites Ice Shelf (with the necessary ice thickness to reach the depth of the flat-topped surfaces). A value of ∼ 400-500 m is similar to ice-shelf thicknesses for Thwaites Ice Shelf today (Griggs and Bamber, 2011;Jordan et al, 2020), and a prevalence of flat-topped highs at this depth may, therefore, support recent modification of the sea-floor highs at TG. In contrast, the deeper flat top of H3 (640 m depth) was probably formed at an earlier stage, as was the flat top of the high in Pine Island Trough, as that area is known to have been ice-free (sheet and shelf) for at least the last 10 kyr (e.g.…”
Section: Bathymetric Highs and Ridgessupporting
confidence: 56%
See 4 more Smart Citations
“…We suggest that this morphology was generated as the highs were overridden and eroded by a formerly expanded TG and Thwaites Ice Shelf (with the necessary ice thickness to reach the depth of the flat-topped surfaces). A value of ∼ 400-500 m is similar to ice-shelf thicknesses for Thwaites Ice Shelf today (Griggs and Bamber, 2011;Jordan et al, 2020), and a prevalence of flat-topped highs at this depth may, therefore, support recent modification of the sea-floor highs at TG. In contrast, the deeper flat top of H3 (640 m depth) was probably formed at an earlier stage, as was the flat top of the high in Pine Island Trough, as that area is known to have been ice-free (sheet and shelf) for at least the last 10 kyr (e.g.…”
Section: Bathymetric Highs and Ridgessupporting
confidence: 56%
“…Troughs and channels in the adjacent part of Pine Island Bay have been described comprehensively by Nitsche et al (2013) and Kirkham et al (2019). The larger troughs in our study area, which have also been identified on gravity-derived regional bathymetry maps (Millan et al, 2017;Jordan et al, 2020), are considered important as potential pathways for the transport of CDW towards the grounding zone of TG and warrant full description here. We distinguish these comparatively larger troughs, based on their size, connectivity and variable flank form (as described above), from the channels which are notably smaller in scale (Fig.…”
Section: Trough and Channel Metricsmentioning
confidence: 78%
See 3 more Smart Citations